Going electric: Expert survey on the future of battery technologies for electric vehicles - Michela Catenacci; Elena Verdolini; Valentina Bosetti; Giulia Fiorese; Nadia Ameli (Fondazione Eni Enrico Mattei (FEEM), 2012)
The paper describes the results of a survey, carried out with leading EU experts, on the capacity of both fully electric and plug-in hybrid vehicles to reach commercial success in the next twenty years. The success of electric transport is hampered by a combination of low range, scarce efficiency and high costs of batteries. Costs are expected to decrease in response to increasing sales volume and technical improvements, and advances would result from adequate investments in research, development and demonstration (RD&D). Experts' judgements are collected to shed light on the inherently uncertain relationship between RD&D efforts and consequent technical progress, and to assess the complex dynamics that will hinder or support the widespread diffusion of electric vehicles. The analysis of the experts' data results in a number of important policy recommendations to guide future RD&D choices and target commitments both for the EU and its member states.
Keywords: Q5; Q55; 330; Expert Elicitation; Battery Technologies; Electric Vehicles; Elektrofahrzeug; Batterie; Elektrische Energietechnik; Forschung; Europa